How can bots be an interesting tool for traditional banks to engage with millennials - Alarcão, Francisco Maria Santos Silva de Noronha de (2018)
This thesis’ purpose is to study how a bot can be an interesting tool for traditional banks to get closer to millennials and gain back the interest and trust of its customers. Even though this technology is only beginning to integrate the market, it is an innovative tool with the ability to offer the convenience and speed customers demand. The goal of this study is to understand if the relationship between the customer and the bank, the client’s profile, the functionalities the service can have and the platform in which it is used can influence the interest in using this innovation. To reach this goal, the author created a survey to analyze the impact of all the referred aspects. Besides the analysis done about this technology, the traditional banks’ reality is also taken under analysis, to act as support in strategic decisions and show how this technology can be inserted and create a positive impact in this specific context. Through a statistical analysis, it was possible to understand that the weakest the relationship between costumers and their bank the biggest the interest in using this technology, though the influencer isn’t the relationship itself but what the service can offer. This way, the functionalities that potentiate the usage of a bot are: the ability to make payments and transfers, search for information and make investments. Finally, the results also shown that consumers intend to interact with the bank through its available digital platforms, more specifically the mobile app and website.